Evangelism made slightly less difficult : how to interest people who aren't interested - Pollard, Nick. (Nottingham, UK: InterVarsity Press, 2004)
They are quite satisfied with their lives, quite content with their beliefs, and see no need to change. So how can we get them interested and make evangelism just slightly less difficult? Nick Pollard has been doing this for years and has some ideas on how we can do it too. This book explains why people think the way they do and offers some practical suggestions on how to reach them. The author shows how we can break through the barrier of disinterest and help people want to know about Jesus and why he can and should make a difference in their lives. He also provides ways to answer their tough questions and lead them in their first steps to faith in Christ.
Includes bibliographical references
Keywords: Evangelistic work; Witness bearing (Christianity)